THE ELECTRONIC ARBITRATION SYSTEM IN THE UNITED ARAB EMIRATES - OmarNadhmi, Basma Amer (Antis Publisher, 2025)
Objective: The rapid expansion of electronic commerce has created new legal challenges, particularly in resolving disputes arising from electronic contracts, and this study seeks to clarify the concept and procedures of electronic arbitration in the UAE, examine its technical and legal environment, and evaluate its capacity to serve as a legislative model for other countries. Method: The UAE has addressed these challenges by introducing comprehensive legislation, most notably Federal Law No. 6 of 2018 on arbitration, supported by amendments to the Civil Procedures Law and specialized arbitration centers. Result: Findings reveal that the UAE has successfully created a robust framework that integrates electronic communication technologies with arbitration procedures, supported by advanced infrastructure, specialized centers, and enforceable legal rules, making it distinct within the Arab region. Novelty: Unlike traditional approaches, the UAE’s system institutionalizes electronic arbitration through dedicated laws, modernized technical infrastructure, and specialized centers, demonstrating that adopting electronic arbitration not only enhances efficiency, transparency, and fairness but also provides a legislative reference point for other nations seeking to regulate electronic dispute resolution in line with international practices.